Essential Oil Composition of Wiedemannia Fisch. & C.A. Mey. Genus from Turkey: A Chemotaxonomic Approach - Kilic, Omer; Bagci, Eyup (Taylor & Francis Ltd, 2014)
The essential oils water distilled aerial parts of Wiedemannia orientalis Fisch. & C.A.Mey. and Wiedemannia multifida (L.) Benth. (Lamiaceae) were investigated by GC and GC-MS. Thirty seven and thirty six compounds were identified comprising representing 93.4 % and 94.9 % of the total components in the oils, respectively. Germacrene D (23.3 %), thymol (16.4 %) and carvacrol (12.3 %) in W. orientalis; germacrene D (29.8 %), thymol (19.3 %) and beta-caryophyllene (13.9 %) were identified as major components in W. multifida. The chemical distribution of the essential oil compounds in the genus pattern were discussed in means of chemotaxonomy and natural products.
Keywords: Germacrene D; Thymol; Lamiaceae, Essential oil; Wiedemannia